A discourse on RPG metanoia using a structural analysis and sociocultural approach - Briones, John Nathaniel B. (2014.)
This paper is a study on RPG Metanoia, a Filipino computer generated film released in December 2010. The film features a hero and his adventure in real life and as a player of the Massively Multiplayer Online Role Playing Game Metanoia. This thesis will be studying RPG Metanoia for the sake of adding academic knowledge regarding computer games themed media and pop culture in literature. Using analysis by Vladimir Propp RPG Metanoia will be subject to formalist structuralism in order to analyze the literary structure of the film. A study by Catherine Gallagher and Stephen Greenblatt will supplement the thesis in order to address structuralism?s limitations and to give this analysis more depth via a socio-cultural approach. Objectives include the intent for analyzing the film via structuralism, comparing the film to related games and media, and studying the film via a socio-cultural perspective. Findings include the successful dissection of the film and proper categorization of each scenario to Propp?s analysis? functions. Also, New Historicism provides facts supporting the significance of the film as a reflective piece of literature on a particular prevailing attitude Filipinos towards games. Finally, the study also provides a brief comparison and analysis of the games related to RPG Metanoia and reveals the inspiration and motivation behinds the conceptualization of the film. The conclusion confirms RPG Metanoia as a legitimate literary narrative as well as label it as falling under the category of literature structurally similar to folk tales. It also highlights several points regarding the importance of the film as a literary fantasy referencing to the effects of games and technology of the Philippines? youth and culture.
Thesis -- Bachelor of Arts in Literature. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Metanoia; Structural analysis